2014
DOI: 10.1021/ma500420w
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport in Nanostructured PS–PEO–PS Triblock Copolymer Electrolytes

Abstract: Nanostructured block copolymer electrolytes (BCE) are currently attracting widespread interest for applications in rechargeable lithium batteries. In order to investigate the influence of the composition, and therefore that of confinement, on the conductivity, a series of triblock PS− PEO−PS copolymers, with three linear PEO blocks of molecular weights 9, 10, or 35 kg mol −1 and with PEO weight fractions varying from 36% to 75%, were synthesized and doped with LiTFSI. Measurements by impedance spectroscopy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
115
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(120 citation statements)
references
References 52 publications
5
115
0
Order By: Relevance
“…Interestingly, Wang et al 14 observed Arrhenius behavior over the same temperature range with poly[styrene-block-(styrene-graf t-ethylene oxide)-block-styrene] produced by grafting-from polymerization, a difference possibly related to architecture or grafting density effects. The BBCPs described herein demonstrate similar or moderately higher conductivity than lithium-doped linear PEO-containing block copolymers such as PS−PEO, 27 PS− PEO−PS, 6 and PP−PEO−PP. 7 The comparable conductivity, especially at such low PEO molecular weights, is perhaps surprising since the brush architecture effectively dilutes the volume fraction of the conducting PEO domain with norbornene end groups (in the case of gPS 11 -gPEO 78 -gPS 11 by about 10%), a consideration that has previously been assumed to decrease conductivity.…”
Section: Macromoleculesmentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, Wang et al 14 observed Arrhenius behavior over the same temperature range with poly[styrene-block-(styrene-graf t-ethylene oxide)-block-styrene] produced by grafting-from polymerization, a difference possibly related to architecture or grafting density effects. The BBCPs described herein demonstrate similar or moderately higher conductivity than lithium-doped linear PEO-containing block copolymers such as PS−PEO, 27 PS− PEO−PS, 6 and PP−PEO−PP. 7 The comparable conductivity, especially at such low PEO molecular weights, is perhaps surprising since the brush architecture effectively dilutes the volume fraction of the conducting PEO domain with norbornene end groups (in the case of gPS 11 -gPEO 78 -gPS 11 by about 10%), a consideration that has previously been assumed to decrease conductivity.…”
Section: Macromoleculesmentioning
confidence: 78%
“…This trade-off motivates the investigation of block copolymers (BCPs) as PEMs, which naturally decouple conductive domains from those providing mechanical support, facilitating independent optimization of both properties. 4 Most BCPs studied to date for battery applications comprise linear architectures incorporating PEO integrally in the backbone, for instance poly(styrene-block-ethylene oxide) (PS−PEO), 5 poly(styrene-block-ethylene oxide-block-styrene) (PS−PEO−PS), 6 and poly(propylene-block-ethylene oxideblock-propylene) (PP−PEO−PP). 7 While other intrachain connectivity has been well-studied with homopolymers and statistical copolymers, 8−12 literature on side-chain grafted BCPs remains limited to single-block functionalization 13−15 and dendrimers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Here, we observe only a topological effect, because of the tortuosity of the conductive PEO domains that increases when the volume fraction of PEO decreases. 31 For these electrolytes, the conductivity data trend line lies between those of SEO 35 S and SEO x S with x < 35. As seen previously, for ϕ c > 0.73 the PS proportion is not sufficient to produce a self-standing film.…”
Section: Chemistry Of Materialsmentioning
confidence: 82%
“…This result is in agreement with literature data for diblock or triblock copolymer electrolytes. 17,31 It has been interpreted as the effect of the dead zone at the interface between the PEO and PS domains. 31 The proportion of this dead zone increases when the M n of PEO decreases, leading to a decrease in the conductivity because the effective volume fraction of the conducting phase decreases.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…[23][24][25] In studies utilizing block copolymers as solid polymer electrolytes, the mechanical phase is usually made of a high glass transition temperature polymer such as polystyrene. [26][27][28][29] Extensive work on the thermodynamics of polystyrene-b-poly(ethylene oxide) (SEO) diblock copolymers [30][31][32][33] indicate that the tendency for microphase separation is enhanced by the presence of ions. 34,35 For symmetric SEO electrolytes, i.e.…”
mentioning
confidence: 99%